Pengaruh Pemberian Koro Benguk (Mucuna pruriens L) terhadap Kadar Gula Darah Tikus Diabetes Melitus yang Diinduksi Streptozotocin - Endang Widhiyastuti; Mastuti Widi Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Diabetes which is well-known in the community as diabetes in Indonesia is a chronic disease, which occurs when the pancreas does not produce enough insulin or when the body cannot utilize the insulin produced by its own products. The Provision of antioxidants in DM mice can reduce blood sugar levels. One of the herbs that can be used for control and management of blood sugar in diabetes is swollen koro. Koro Benguk (Mucuna pruriens L) is a plant that can be used as an alternative treatment because it contains antioxidants that can maintain health without causing toxic effects. The purpose of this study was to determine whether there is an effect of giving koro benguk coffee (Mucuna pruriens L) on blood sugar levels of Streptozotocin-induced Diabetes Mellitus Rats. This study is an experimental study of Sprague Dawley mice. A total of 35 male wistar rats were divided into 5 groups each: normal control (K1); diabetes control (K2); diabetic rats were given a large coffee extract 0.63 mg / g BW rat (P1); diabetic rats were given a large infusion of coffee koro 1.26 mg / g BW rats (P2). Diabetic rats were given an infusion of coffee koro benguk20,52 mg / g BW rats. Fasting blood glucose (GDP) levels were analyzed weekly for 3 weeks using the GOD-PAP method. The results of the study showed a decrease in blood sugar for 4 times the observation time in almost all treatment groups except the positive control group. The conclusions in this study were the provision of related coffee (Mucuna pruriens L) can reduce fasting blood glucose levels in Sprague Dawley rats with diabetes models significantly compared to controls.